Abundance estimates of southern right whales (Eubalaena australis) in Bahía San Antonio, Patagonia, Argentina - Vermeulen, Els (J. Cetacean Res. Manage., 2023)
The abundance of southern right whales (Eubalaena australis) was estimated by the means of aerial line-transect surveys for the area of Bahía San Antonio, a bay located in the north-western region of the San Matías Gulf (40°50’S 64°50’W), Rio Negro, Patagonia Argentina. In total, seven aerial surveys were conducted in the first week of August and September 2009, September, October and November 2010, and August, September 2011. Survey effort equalled a total flight time of 12.4h, during which 200 whales were counted in 119 whale groups. Half of the encounters were solitary animals and 17% were mating groups. Corrected abundance estimates showed the highest amount of whales present in the bay during the month of September, with 85±71, 207±108 and 117±55 animals in 2009, 2010 and 2011 respectively. In adjacent months, less than half the amount of whales seemed to be present. The correction factor g(0)availability resulted 0.392±0.456. Perception bias was not accounted for. These aerial surveys resulted in the first estimates of southern right whale abundance in this north Patagonian bay and indicated a rather abrupt peak during the month of September. This being the peak month for right whale presence is consistent with data from other regions in the Southwest Atlantic, but data obtained in the other months remained scarce and thus results should be interpreted carefully. The complete absence of whales in the area during November 2010 and August 2011 raises further questions on the predictability of the whale’s presence in the area. Overall, more consistent aerial surveys should be conducted to accurately determine the annual and interannual evolution of southern right whale abundance in the study area.